Analysis of the Relationship between Knowledge, Perception, Attitude, and Behavior of Emergency Room Nurses Toward Interprofessional Colaboration - Widyastuti, Dwi; Milkhatun, Milkhatun; Handayono, Priyo; Jannah, Devi Nurul; Abidah, Aqmarina; Adila, Lisa (Global Health Science Group, 2024)
As the main health worker in the Emergency Room (ER), nurses have a strategic approach to improving interprofessional communication and coordination. Effective professional collaboration is facilitated by the knowledge, skills, attitudes and behavior of nurses in the Emergency Room. Objective to analyze the relationship between knowledge, perceptions, attitudes and behavior of nurses towards inter-professional collaboration. This research is a quantitative research with a cross sectional approach to analyze the relationship between knowledge, perceptions, attitudes and behavior of nurses towards inter-professional collaboration. The research population was 59 ER nurses. The sampling technique used was total sampling. Data was collected by a questionnaire on nurses'' knowledge, perceptions, attitudes and behavior using observation sheets. Data analysis used the Kolmogrov-Smirnov normality test, and the correlation test used Kendall Tahu. The majority of nurses'' knowledge is in the sufficient category, 32 respondents (59.5%), and the perception of nurses in the good and bad categories is same, namely 27 respondents (50.5%). The majority of nurses'' attitudes were in the positive category of 29 respondents (53.7%), and the behavior of nurses was in the good category 38 respondents (70.4%). Data is normally distributed. The Kendall Tau test shows that there is a relationship between knowledge, perceptions, attitudes, and behaviors of emergency room nurses towards interprofessional collaborative practices. Every healthcare professional needs specific instructions on inter-professional collaboration in order to understand their respective responsibilities and roles. Additionally, nurses' self-development needs to be improved in order for them to comprehend inter-professional cooperation adequately through ongoing education and professional collaboration training.